Historical economic returns to alternative swine enterprises in Kansas - Jones, R.; Langemeier, Michael R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This study examines historical net returns to average Kansas swine producers over the past 16 years. Swine production has been a profitable enterprise. As expected, average returns per head have been higher for farrow-to-finish producers than for feeder pig finishers, and farrow-to-finish producers have nearly always been able to at least cover variable costs of production.
Keywords: Swine; Net returns; Variable costs; Total costs